(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The aim of this study is to observe the concrete resistance towards acid attack. This is studied on M40 grade concrete, in which 5% by weight of binder is replaced with metakaolin and fine aggregate is replaced partially with the range of 5 to 20% by marble sludge powder and green sand simultaneously. Four different mixes other than control mix is taken for this study. The 100mm cubes are casted, cured and average compressive strength is compared with conventional concrete and those cured under two different acids. The two different acids taken for this study are Hydrochloric Acid and Sulphuric Acid. The average percentage loss of weight and average compressive strength of cubes before and after two different acids for all the mixes are investigated. From the experimental results, it is inferred that the control mix when cured under both 1% concentrated HCl and H2SO4 solutions showed a high loss in weight comparing with modified concrete. The increase in marble powder and green sand upto 10% by weight of fine aggregate gives high reduction in loss of weight. The mix with 10% marble powder and green sand offered comparatively better solutions insisting the concrete modified with the same can be recommended for making good and acid resisting concrete.